In the midst of winter [large type] : a novel - Allende, Isabel (Thorndike Press large print basic, 2017)
In the middle of a snowstorm in Brooklyn, 60-year-old human rights scholar Richard Bowmaster hits the car of Evelyn Ortega, a young, undocumented immigrant from Guatemala. What at first seems just a small inconvenience takes a far more serious turn when Evelyn turns up at the professor's house seeking help. At a loss, the professor asks his tenant Lucia Maraz, a 62-year-old lecturer from Chile, for her advice. These three very different people are brought together in a story that moves from present-day Brooklyn to Guatemala in the recent past to 1970s Chile and Brazil, sparking the beginning of a long overdue love story between Richard and Lucia.